TINNITUS MANAGEMENT AND ALLEVIATION HUB - Mumza Zafar,; Sarah Ramzan,; Ayesha Imran,; Aasma Khalid,; Sobia Riaz, (Spectrum of Engineering Sciences, 2025)
Tinnitus is a ordinary disorder of the auditory system in which a person acumen sound when no extrinsic sound is present. Tinnitus is affecting the lives of millions of people in the world. The major aim of developing a mobile-based Tinnitus management and alleviation hub is to deal with the person suffering from tinnitus, After answering the questionnaire accurately severity will be checked if a person has mild/moderate or severe tinnitus. Based on tinnitus severity CBT Exercises and sound therapy will be provided. People with severe tinnitus will be provided to nearby doctors for extensive support. The severity of tinnitus will be assessed with the help of sound tests and data analysis. Personalized therapy will be recommended to persons which includes soothing sounds for non- Muslims and nasheeds for Muslims. Moreover, the person with severe tinnitus will be provided with nearby healthcare professionals detail information and locations. In addition, our platform contains a chatbot that will facilitate users with queries. The project contains a userfriendly interface so that a large number of users can engage with the application and they can get relief from tinnitus.